Analisis Tingkat Kekumuhan dan Faktor Penyebab Kawasan Permukiman Kumuh di Kelurahan Kebonsari Kabupaten Jember - Alifan Cahyana; Wahyuningtiyas, Loetvy; Alvandio, Christopher (Reinforcement Review in Civil Engineering Studies and Management, 2025)
Slum settlements are a major challenge in urban development, significantly affecting the quality of life of residents. This study aims to analyze the level of slum conditions and identify the factors causing slum settlements in RT.003 RW.018, Kebonsari Subdistrict, Jember Regency. The research employed a mixed-method approach, combining qualitative and quantitative methods through observation, interviews, and documentation. The assessment of slum level refers to seven main aspects in accordance with Regulation of the Minister of Public Works and Public Housing No. 14/PRT/M/2018. The results show that the slum level in RT.003 RW.018 is classified as light, with an average score of 45.93%, although there are significant problems in building conditions and waste management. Basic infrastructure such as neighborhood roads, drainage, and access to drinking water is relatively adequate, but wastewater management and community participation in maintaining the environment still need improvement. The main factors causing slum conditions are building irregularities, limited land, and low community awareness and participation. This study highlights the importance of an integrated approach that combines physical improvement and social empowerment to create a sustainable residential environment.